Radiologic imaging of the renal parenchyma structure and function - Grenier, Nicolas; Merville, Pierre; Combe, Christian (Nature reviews. Nephrology, 2016)
Key Points Radiologic techniques can be used to assess gross renal morphology, but morphological changes at this level show poor correlation with renal function and the changes over time are often nonspecific Dynamic contrast-enhanced CT or MRI can provide haemodynamic information, such as renal blood flow or tissue perfusion, which can facilitate personalized patient management Information obtained from blood oxygen level-dependent MRI could contribute to the understanding of chronic kidney disease pathophysiology, but technical issues remain to be solved before large-scale clinical use MRI and renal scintigraphy can both provide a measure of split renal function in moderately dilated kidneys, but radiological measurement of single kidney glomerular filtration rate requires further development The ability to identify fibrotic changes and inflammatory components in damaged renal tissue by radiologic imaging is a major goal for future research Radiologic techniques are routinely used to assess tissue macrostructure and gross morphology. In this Review, Nicolas Grenier and colleagues discuss how technological advancements in CT, MRI, and ultrasonography have faciliated the assessment of organ microstructure and function, and how these techniques can be applied to the kidney. They outline the benefits of incorporating radiologic data with routine clinical diagnostics, and the technical challenges that remain to be addressed when imaging the kidney. Radiologic imaging has the potential to identify several functional and/or structural biomarkers of acute and chronic kidney diseases that are useful diagnostics to guide patient management. A renal ultrasound examination can provide information regarding the gross anatomy and macrostructure of the renal parenchyma, and ultrasound imaging modalities based on Doppler or elastography techniques can provide haemodynamic and structural information, respectively. CT is also able to combine morphological and functional information, but the use of CT is limited due to the required exposure to X-ray irradiation and a risk of contrast-induced nephropathy following intravenous injection of a radio-contrast agent. MRI can be used to identify a wide range of anatomical and physiological parameters at the tissue and even cellular level, such as tissue perfusion, oxygenation, water diffusion, cellular phagocytic activity, tissue stiffness, and level of renal filtration. The ability of MRI to provide valuable information for most of these parameters within a renal context is still in development and requires more clinical experience, harmonization of technical procedures, and an evaluation of reliability and validity on a large scale.